Bibliometric analysis of Laminated Timber In Building Structures: 2015-2025 - Simon Petrus Hamonangan Simorangkir; Muhammad Irwansyah (Jurnal VORTEKS, 2026)
The increasing adoption of laminated timber products (e.g., glulam and CLT) in modern construction requires a systematic mapping of the scientific landscape to understand research trajectories, collaboration patterns, and the ongoing shift toward sustainability-related topics. This study aims to map the development of laminated timber research during 2015–2025 through bibliometric analysis, covering publication trends, dominant subject areas, leading sources, productive authors, keyword evolution, and thematic structures. Prior studies are often descriptive or limited to specific technical aspects, while large-scale, metadata-driven quantitative mapping remains relatively limited. The novelty lies in integrating quantitative analysis using RStudio with network-based science mapping using VOSviewer to provide a more comprehensive overview (trends, co-occurrence networks, thematic maps, and topic shifts). Publication data were mined from Scopus, yielding 1,875 documents (2015–2025), and then analyzed and visualized using RStudio (data cleaning, descriptive statistics, trend analysis) and VOSviewer (network, overlay, and density visualizations). The results indicate a strong growth in publications with a peak around 2023, dominance of Engineering-related contributions and structural/material-focused outlets, and a noticeable shift from mechanical-performance studies toward sustainability and environmental impact themes, highlighting opportunities for deeper cross-disciplinary integration in future research